Como os professores ensinam botânica no ensino médio em São José Dos Campos – SP? - Carvalho, Nathália; de Mattos Pereira Mano, Amanda; Linhares Granemann de Medeiros, Jucelia (Góndola, enseñanza y aprendizaje de las ciencias, 2025)
Studies on Botany education in the scientific field have gained prominence in recent years, mainly due to the inefficacy of traditionally adopted pedagogical practices, which contribute little to meaningful learning. These methodologies are mostly based on traditional teaching approaches, limiting student engagement. In contrast, active methodologies shift the focus from the teacher to the student, fostering a more participatory learning process and potentially addressing some of the gaps in Botany education. Given these challenges, this study highlights the importance of school practices that encourage interaction in the classroom to enhance the teaching-learning process in this subject. In this context, the research aimed to identify the methodologies and didactic tools used by high school Biology teachers in Botany classes. To achieve this, a qualitative approach was adopted, using semi-structured interviews as a data collection instrument. The study involved 17 teachers from 10 public schools in São José dos Campos, São Paulo, Brazil. The collected data were analyzed using Content Analysis. The findings indicate that, although some teachers seek to diversify their teaching strategies, lecture-based classes, primarily supported by slide presentations, still prevail among the respondents, reinforcing the persistence of traditional practices. It is noteworthy that this approach has been entrenched in school environments for decades, and breaking away from such well-established models remains a challenge for many educators. However, some initiatives emphasize student protagonism, which may inspire new perspectives and drive transformations in the teaching practices of these subjects.